Ontology-based Semi-automatic Workflow Composition - de Oliveira, Daniel; Ogasawara, Eduardo; Dias, Jonas; Baião, Fernanda; Mattoso, Marta (Journal of Information and Data Management, 2012)
Due to the growing complexity of scientific workflows, it is important to provide abstraction levels to aid scientists to compose these workflows. By doing this, we isolate scientists from infrastructure issues and let them focus on their domain of expertise when composing the workflow. Although using abstract workflows is a first step, there are many open issues, such as the ones related to semantics. Adding semantics to abstract workflows enables the explicit representation of which activities can be linked to each other, or which activities are similar to each other. Existing approaches address either the representation of abstract workflows or using domain ontologies to add semantics to workflow activities, but not both. In the latter case, these approaches focus only on adding semantics to executable workflows, instead of abstract ones. This makes it difficult to group executable workflows into a common abstract representation in the conceptual level. This article proposes coupling a workflow ontology, named SciFlow, to an abstract workflow representation named Experiment Line and implemented in the GExpLine tool. This is a step towards semantic mechanisms, helping scientists to identify equivalent activities or grouping executable activities into one abstract activity with the same semantics.